Amber: Decoupling User Data from Web Applications - Chajed, Tej; Gjengset, Jon; Hooff, Jelle van den; Kaashoek, M. Frans; Mickens, James; Morris, Robert; Zeldovich, Nicholai (USENIX - Advanced Computing Systems Association, 2015)
User-generated content is becoming increasingly common on the Web, but current web applications isolate their users’ data, enabling only restricted sharing and cross-service integration. We believe users should be able to share their data seamlessly between their applications and with other users. To that end, we propose Amber, an architecture that decouples users’ data from applications, while providing applications with powerful global queries to find user data. We demonstrate how multi-user applications, such as e-mail, can use these global queries to efficiently collect and monitor relevant data created by other users. Amber puts users in control of which applications they use with their data and with whom it is shared, and enables a new class of applications by removing the artificial partitioning of users’ data by application.